Preliminary study of reverse supply chain development in Indonesia - Maulida Boru Butar Butar; Stephanus Benedictus Bera Liwun (JENIUS : Jurnal Terapan Teknik Industri, 2023)
As a developing country, Indonesia is experiencing various advances, including in the industrial sector. A supply chain is a science that has long been studied and explored by many academics and practitioners. That part of the supply chain referred to as the opposite is the reverse supply chain or what is widely known as the Reverse Supply Chain (RSC). This article will present preliminary studies about RSC development in Indonesia. RSC in Indonesia particularly has been studied by a lot of researchers. However, most discussions are limited to reverse logistics and waste management. An explanation of the existing RSC in Indonesia will be discussed and provided. In Indonesia, most RSC activities happen in small and medium companies that have yet to gain experience or knowledge that they have been practicing RSC. The people's purchasing power which is still quite low has made small and medium industries in the refurbished sector grow rapidly. This paper will explain what a reverse supply chain is and how the development of this study is based on the existing literature. It is also a discussion of how the reverse supply chain application in Indonesia and what steps can be taken to improve the performance of the reverse supply chain in Indonesia